Seroprevalence of Rift Valley fever virus in sheep and goats in Zambézia, Mozambique. Issue 1 (1st January 2016) - Blomström, Anne-Lie; Scharin, Isabelle; Stenberg, Hedvig; Figueiredo, Jaquline; Nhambirre, Ofélia; Abilio, Ana; Berg, Mikael; Fafetine, José
Abstract : Background: The Rift Valley fever virus (RVFV) is a vector-borne virus that causes disease in ruminants, but it can also infect humans. In humans, the infection can be asymptomatic but can also lead to illness, ranging from a mild disease with fever, headache and muscle pain to a severe disease with encephalitis and haemorrhagic fever. In rare cases, death can occur. In infected animals, influenza-like symptoms can occur, and abortion and mortality in young animals are indicative of RVFV infection. Since the initial outbreak in Kenya in the 1930s, the virus has become endemic to most of sub-Saharan Africa. In 2000, the virus appeared in Yemen and Saudi Arabia; this was the first outbreak of RVF outside of Africa. Rift Valley fever epidemics are often connected to heavy rainfall, leading to an increased vector population and spread of the virus to animals and/or humans. However, the virus needs to be maintained during the inter-epidemic periods. In this study, we investigated the circulation of RVFV in small ruminants (goats and sheep) in Zambézia, Mozambique, an area with a close vector/wildlife/livestock/human interface. Materials and methods: Between September and October 2013, 181 sheep and 187 goat blood samples were collected from eight localities in the central region of Zambézia, Mozambique. The samples were analysed for the presence of antibodies against RVFV using a commercial competitive ELISA. Results and discussion: The overall seroprevalence was higher in sheep (44.2%) than goats (25.1%); however, there was a high variation in seroprevalence between different localities. The data indicate an increased seroprevalence for sheep compared to 2010, when a similar study was conducted in this region and in overlapping villages. No noticeable health problems in the herds were reported. Conclusions: This study shows an inter-epidemic circulation of RVFV in small ruminants in Zambézia, Mozambique. Neither outbreaks of RVF nor typical clinical signs of RVFV have been reported in the investigated herds, indicating subclinical infection.